COVID-19 outbreak: current scenario of Pakistan. (May 2020) - Waris, A.; Atta, U.K.; Ali, M.; Asmat, A.; Baset, A.
Abstract: COVID-19 outbreak was first time experienced in the Wuhan City of China at the end of December 2019. Which spread rapidly in China and then worldwide in 209 countries of America, Europe, Australia and Asia including Pakistan. There are more than fifty thousand mortalities and one million plus people have been affected worldwide, while figure increases rapidly. Different steps have been taken worldwide for the control of COVID-19. Even with less resources Pakistan also taken rigorous measures like designed special hospitals, Laboratories for testing, quarantine facilities, awareness campaign and lock down to control the spread of virus. We highlighted the efforts of government to combat this deadly pneumonia.